A review of the genus Enicospilus Stephens (Ichneumonidae: Ophioninae) from Vietnam, with descriptions of ten new species – Corrigendum - Pham, Nhi Thi; Pham, Phu Van; Matsumoto, Rikio; Shimizu, So; Broad, Gavin R. (European Journal of Taxonomy, 2023)
The present corrigendum corrects an error that occurred in Pham et al. (2023). https://doi.org/10.5852/ejt.2023.873.2133